Correction. Hungry runners – low energy availability in male endurance athletes and its impact on performance and testosterone: mini-review - The Publisher (European Journal of Translational Myology)
In the paper titled “Hungry runners – low energy availability in male endurance athletes and its impact on performance and testosterone: mini-review”, published in vol. 33, issue 2 of 2023, Supplementary Table 1 was mistakenly mentioned as Table 1. The correct supplementary file is now available.